UPAYA SEKURITISASI INDONESIA TERHADAP LAUT NATUNA UTARA PASCA SENGKETA PERBATASAN DENGAN TIONGKOK PADA TAHUN 2016 - Prayoga, Adhit; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
One-sided claim by the Chinese Government through the Nine-Dash Line and illegal fishing by neighboring countries such as Malaysia and Vietnam justify an obvious threat to Indonesian sovereignty with all the potential contained in it. Considering the emerging intensity of these illegal actions, several securitization attempts were needed for North Natuna Sea. This research was prepared using the perspective of Neorealism, the theory of securitization and the concept of maritime security. This research used descriptive qualitative research methods which the research data was obtained through literature review and interviews with relevant stakeholders. This research had been carried out in Jakarta for 4 months. The results of this research indicates that Indonesia had done a variety of securitization efforts e.g developing military and non-military aspects as well as conducting field operations. These attempts succeeded in enhancing the level of compliance, thereby reducing illegal actions in Indonesian waters and indirectly increasing the welfare of the people.Keywords: Sovereignty Claim, Illegal Fishing, North Natuna Sea, Military and Non-Military Development, Field Operations.